Cover Image, Volume 173A, Number 10, October 2017. Issue 10 (October 2017) - Bashir, Rani A.; Dixit, Abhijit; Goedhart, Caitlin; Parboosingh, Jillian S.; Innes, Allan M.; ,; Ferreira, Patrick; Hasan, Shabih U.; Au, Ping‐Yee B.
Abstract : The cover image, by Rani A. Bashir et al., is based on the Original Article Lin‐Gettig syndrome: Craniosynostosis expands the spectrum of the KAT6B related disorders, DOI:10.1002/ajmg.a.38355 .